2007
DOI: 10.1111/j.1570-7458.2007.00632.x
|View full text |Cite
|
Sign up to set email alerts
|

Diadegma mollipla parasitizing Plutella xylostella: host instar preference and suitability

Abstract: Oviposition decisions (i.e., host selection and sex allocation) of female parasitoids are expected to correspond with host quality, as their offspring fitness is dependent on the amount and quality of resources provided by a single host. The host size model assumes that host quality is a linear function of host size, with larger hosts believed to contain a greater quantity of resources, and thus be more profitable than smaller hosts. We tested this assertion in the laboratory on a solitary larval-pupal parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 58 publications
(91 reference statements)
0
7
1
3
Order By: Relevance
“…Both theories stress that there were trade-offs between maternal fitness through host-feeding [27][28] and enhanced reproduction through oviposition on the same host individual as used for host-feeding [9], [29]. However, we found that optimum foraging strategy was combined with optimum oviposition strategy.…”
Section: Discussioncontrasting
confidence: 54%
“…Both theories stress that there were trade-offs between maternal fitness through host-feeding [27][28] and enhanced reproduction through oviposition on the same host individual as used for host-feeding [9], [29]. However, we found that optimum foraging strategy was combined with optimum oviposition strategy.…”
Section: Discussioncontrasting
confidence: 54%
“…We speculate that 3 or 4-day old pupae may provide better nutritional quality than pupae of other ages. Other parasitoid species, i.e., Diadromus collaris (Wang & Liu 2002), Diadegma mollipla (Nofemela 2008) and Microplitis mediator (Li et al 2006), also showed a preference for hosts of a particular age.…”
Section: Discussionmentioning
confidence: 95%
“…Pupae that did not suffer parasitism were those that had the lowest weight. Parasitoid females look for the largest possible host, as it will possibly have the greatest quantity and quality of food resources for their offspring (Lin and Alves, 2003;Nofemela and Kfir, 2008). Non-parasitism of pupae 5 and 6 may be linked to the quality of the host.…”
Section: Introductionmentioning
confidence: 99%